Palbociclib and dsRNA sensor co-operate to enhance anti-cancer effects through ER stress and modulation of immune evasion - Victoria Roulstone; Joan Kyula-Currie; James Wright; Emmanuel C. Patin; Isaac Dean; Lu Yu; Aida Barreiro-Alonso; Miriam Melake; Jyoti Choudhary; Richard Elliott; Christopher J. Lord; David Mansfield; et al. (Nature Communications)
Abstract Cytoplasmic pattern recognition receptors (PRR) for double-stranded RNA, such as RIG-I/MDA5, are key mediators of anti-viral responses. Here we screen for synergistic drug-virotherapy combinations and find that the reovirus type III Dearing strain (Rt3D)-palbociclib combination augments oncolytic virus-induced stress responses and increases interferon production and signaling. Data from RIG-I agonist and ER stress-inducing agents further confirms the crosstalk between RNA-sensing and ER stress in inducing cancer cell death and interferon production. Combined Rt3D-palbociclib also increases innate immune activation and IFN-induced HLA expression within tumor cells, with accompanying alterations in the epigenetic landscape and endogenous retroviral (ERV) elements. Analysis of the immunopeptidome in treated cells further reveals changes to HLA-captured peptides, including altered expression of peptides from cancer or testis antigens and ERVs. Our findings thus highlight the crosstalk between stress signaling and PRR activation for mediating enhanced anti-cancer efficacy.